Is there a space for medium-sized cassava seed growers in Nigeria?. Issue 6 (1st November 2020) - Bentley, Jeffery W.; Nitturkar, Hemant; Obisesan, David; Friedmann, Michael; Thiele, Graham
ABSTRACT: Until recently, there has been little commercial sale of vegetatively propagated crop seed, except for potatoes ( Solanum tuberosum ). This is especially true in developing countries. However, a formal, commercial seed sector for cassava ( Manihot esculenta ) is emerging in Nigeria. In 2016, a project, Building an Economically Sustainable Integrated Cassava Seed System in Nigeria (BASICS), started to encourage village farmers to certify and sell cassava seed. A questionnaire survey of 30 cassava entrepreneurs across Nigeria in 2019 included some of those village-based growers as well as larger producers, including some who certified their planting material. In the long run, if there is a consistent demand for certified cassava seed, medium-sized producers may be able to satisfy some of that demand, especially if they have continued programmatic support; otherwise, these budding seed entrepreneurs may close down.